2018
DOI: 10.4103/ajts.ajts_42_17
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of 51 autologous peripheral blood stem cell transplants after uncontrolled-rate freezing (“dump freezing”) using −80°C mechanical freezer

Abstract: BACKGROUND AND OBJECTIVE:Controlled-rate freezing is a complicated, expensive, and time-consuming procedure. Therefore, there is a growing interest in uncontrolled-rate freezing (UCF) with −80°C mechanical freezers for cryopreservation of hematopoietic stem cells. This is a retrospective analysis of efficiency of UCF and outcome of autologous peripheral hematopoietic stem cell (PBSC) transplants at our center from December 2011 to June 2016.MATERIALS AND METHODS:Cryoprotectant solutions used included 5% dimeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…Uncontrolled-rate freezing is not a technically or financially demanding method. This method has been most frequently applied to preserve peripheral blood stem cells with consistent results [ 16 , 17 , 18 , 19 ]. Kumar et al studied various uncontrolled-rate freezing protocols and noted that samples directly stored at −80 °C in 10% DMSO in uncontrolled temperature conditions for a month showed the highest proliferation rate [ 20 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Uncontrolled-rate freezing is not a technically or financially demanding method. This method has been most frequently applied to preserve peripheral blood stem cells with consistent results [ 16 , 17 , 18 , 19 ]. Kumar et al studied various uncontrolled-rate freezing protocols and noted that samples directly stored at −80 °C in 10% DMSO in uncontrolled temperature conditions for a month showed the highest proliferation rate [ 20 ].…”
Section: Discussionmentioning
confidence: 98%
“…The uncontrolled-rate freezing is not a technically or financially demanding technique compared to the previously mentioned methods. Uncontrolled-rate freezing has been most frequently applied for the preservation of peripheral blood stem [ 16 , 17 , 18 , 19 ]. Only a few published studies have described the uncontrolled-rate freezing during subsequent storage of stem cells at −80 ° C [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of the author's knowledge, this is the first such study from India. There are several previous studies from India [9][10][11][12] that have reported long-term complications and transplant outcomes after infusion of cryopreserved HPC. Only one of these studies by Setia et al 12 briefly mentions ASs during the infusion.…”
Section: Discussionmentioning
confidence: 99%
“…There are several previous studies from India [9][10][11][12] that have reported long-term complications and transplant outcomes after infusion of cryopreserved HPC. Only one of these studies by Setia et al 12 briefly mentions ASs during the infusion. However, studying the ASs during the infusion of thawed HPC was not an objective of any of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Поэтому активно растет интерес к процессу замораживания с неконтролируемой скоростью с использованием стандартных морозильных камер, который можно легко адаптировать в условиях ограниченных ресурсов. Тем более, что консервация с неконтролируемой скоростью не приводит к существенному снижению эффективности трансплантации ГСК периферической крови [22]. С целью изучения и проверки более простых и экономичных способов заморозки ГСК, Calvet L, et al (2012) провели клиническое исследование 342 аутотрансплантантов после хранения в течение 3, 6 и 12 мес.…”
Section: методология поискаunclassified